Electrochemical properties of modified poly(4-aminothiophenol)-Zn-Ni MOF-reduced graphene oxide nanocomposite for high-performance supercapacitors. (15th September 2022) - Ensafi, Ali A.; Fazel, Reihaneh; Rezaei, Behzad; Hu, Jin-Song
Graphical abstract: Highlights: Poly(4-aminothiophenol), Zn, Ni, and rGO (PATZ1N2G2-MOF) is fabricated using one-step method. PATZ1N2G2-MOF demonstrated high active surface area and reduced diffusion/transfer pathways. Synergistic effect between the metals in PATZ1N2G2-MOF improved supercapacitor performance. PATZ1N2G2-MOF showed a high specific capacitance of 1230.23F/g at a current density of 1.0 A/g. Asymmetric PATZ1N2G2-MOF//AC supercapacitor demonstrates high energy and power density. Abstract: Metal-organic frameworks (MOFs) have escalated much attention as innovative electrode materials for supercapacitors applications due to their high porosity, adequate active sites, and tunable structures. However, most MOFs show low capacitance, which limits their application in energy storage devices. In this study, a new MOF composite containing poly(4-aminothiophenol) (PAT), Zn, Ni, and reduced graphene oxide (rGO), abbreviated as PATZ1N2G2-MOF, was fabricated by a one-step simple hydrothermal method and its electrochemical characteristics for supercapacitor applications were examined. The structural characterization of the proposed MOF exhibited successful synthesis of a highly porous and nanoscale crystalline spherical PATZ1N2G2-MOF configuration mainly spread on extra thin nano-sheets of rGO. The convenient mixed spherical structure of PATZ1N2-MOF and rGO Nano-sheets facilitates more electrochemically active regions and more accessible routes for charge and mass transfer, developing a specific capacitance as high as 1230.23F g −1 at a current density of 1.0 A g −1 as well as excellent capacitance retention of 89.8% after 3000 repetitive cycles. Moreover, the capacity of the modified positive electrode for the 2-electrode setup was obtained to be 93.31F g −1, producing a high energy and power density of 33.17 Wh kg −1 and 188.35 W kg −1, respectively. The experimental results revealed the superior supercapacitive behavior of the PATZ1N2G2-MOF/NF electrode.